Kompetensi Jurnalis Sebagai Aktor Dalam Produksi Berita Media Multiplatform - Udi Rusadi (Jurnal Studi Komunikasi dan Media, 2012)
Innovations  in  the  field  of  information  and  communication  technology  have  created  the  variety  of information distribution platform to audiences. This is prompted media companies to build and effort to develop system management of news production multiplatform which intended as an effort to keep the media companies alive and growing. By using framework of structuration theory, the pourpose of this study is to reveal the relationship between structure and agency of journalist as actor. The method used is a case study in media companies in South Kalimantan, Banjarmasin Post. The results showed that the duality of structure occurs, which the structure always provides the enabling and the obviouslimitations that cause system technology based newsproduction run. In line with the sructure roles, journalists  as  human  actors  adjust  their  competences  with  management  system  multiplatform.  The system  running  by  the  developing  of  individual  basic  competences  include  discursive  and  practical consciousness, cognitive motivation and soft competences of online media namely attitude of speedy and multi-tasking working and having the work orientation of social networking. Inovasi teknologi komunikasi dan informasi menumbuhkan aneka ragam platform distribusi informasi kepada  khalayaknya.  Hal  ini  mendorong  perusahaan  media  membangun  dan  berusaha mengembangkan sistem manajemen produksi berita multiplatform agar perusahaan media tetap eksis. Dengan  kerangka  pemikiran  teori  strukturasi,  studi  ini  bertujuan  mengungkap  keterkaitan  antara struktur  dan  agensi  dari  para  jurnalis  sebagai  aktor.  Metode  yang  digunakan  ialah  studi  kasus  di perusahaan media Banjarmasin Post di Kalimantan Selatan. Hasilnya menunjukkan, dualitas struktur terjadi, dimana struktur selalu memberikan pemungkin (enable) dan batasan-batasan yang jelas yang menyebabkan  sistem  produksi  berita  berbasis  teknologi  dijalankan.  Sejalan  dengan  peranan struktur tersebut, para jurnalis sebagai  human actormenyesuaikan kompetensinya dengan sistem manajemenmultiplatform yaitu  menjalankan  struktur  dengan  mengembangkan  kompetensi  dasar  meliputi kesadaran  diskursif,  praktis  dan  motivasi  kognitif  dan  mengembangkan  kompetensi  lunak  media onlineyaitu sikap kerja cepat, multitaskingdan memiliki orientasi kerja berjejaring sosial.